(untitled) (Philosophy and Progress, 2019)
In this paper, I will analyze and critically evaluate 20th century American philosopher Robert Nozick’s position regarding utilitarianism; how he refutes utilitarianism with reference to two new concepts called “Experience Machine” and “Utility Monster”. I will argue that if we were given the option of entering into an experience machine as Nozick presented in his book Anarchy State and Utopia, in which we can create a new better life for ourselves, then it would be irrational to refuse the option. I will then reply to Nozick’s objection regarding utilitarianism within his concept of utility monster, where he argued that accepting the theory of utilitarianism causes the necessary acceptance of a utility monster, that is, the condition that some people would use this doctrine to justify the exploitation of others. I will argue here that giving “happy units” to weak utility monsters can bring about wonderful result. All my arguments are formed within utilitarian consequentialist framework. Philosophy and Progress, Vol#61-62; No#1-2; Jan-Dec 2017 P 165-176